COUGH AND CHEST PAIN WITH AN UNCOMMON CAUSE - Das, Indrani; Talukdar, Payel; Das, Kalyan; Verma, Sumit; Makhal, Moloy Kanti (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Multiple Hereditary Exostoses is an autosomal dominant disorder with multiple cartilage capped bony outgrowths in tibia ,fibula, femur, and sometimes the ribs and scapula. They may present with variety of symptoms depending on the structures it compresses such as nerves, arteries or may lead to limb deformities or may cause bursitis , or may undergo malignant transformation. A 33 year old male presented to our outpatient department with recurrent cough and left sided chest pain. On evaluation he was found to have multiple bony outgrowths in the scapula ,5th rib , and limbs. Similar bony outgrowths were also present in his father and grandfather. On clinical and radiological basis a diagnosis of Multiple Hereditary Exostoses was made. His symptoms gradually subsided with removal of the rib and scapular exostoses. Thus evaluation of bony structures should not be overlooked in cases of cough and chest pain. Keywords: Cough, Chestpain, Multiple Hereditary Exostoses.